Generalized Secant Hyperbolic and a Method of Estimate of its Parameters: Maximum Likelihood Modified (2013)
Different generalized distributions are developed in the statistical literature, among them it is the generalized secant hyperbolic distribution (SHG). This paper presents an alternative method for estimation the population parameters of the SHG, called Modified Maximum Likelihood (MVM). Assuming some alternate expressions that are different from Vaughan´s work in 2002, and based on the same set of data from the original source. It is implemented, the transformed method MVM is implemented computationally, it allows us to observe good approximations of the exact values of the parameters of location and scale, presented by Vaughan in his article. The aim is that in the practice you can use a different methodology to estimate.